Maretório: o giro ecoterritorial dos povos extrativistas costeiro-marinhos do litoral da Amazônia paraense do litoral da Amazônia paraense? - LIMA, Paulo Victor Sousa (Universidade Federal do Pará, 2022)
This dissertation presents a reflection on the socio-anthropological construction of the identity of the coastal extractive peoples of the Amazonian coast of Pará. In view of this, the study aimed to understand how the leaders of the National Commission for the Strengthening of Coastal and Marine Extractive Reserves and Extractive Peoples (CONFREM) from Coastal-Marine Extractive Reserves (RESEXs) on the coast of Pará give meaning to the maretório, that by mobilizing it for the recognition of a singular identity, that of coastal-marine extractivistas, they are drawing a concept in practice - as an ecoterritorial turn. It is qualitative exploratory research, which involved a set of techniques and methodological procedures that include bibliographic research, documentary research, and interviews with semi-structured scripts. This material was analyzed in dialog with a proposal of conceptual synthesis of the theoretical field of social movements. However, given the specificities of socio-environmental struggles in the context of the Pará Amazon coast, there was a need to incorporate other analytical categories, such as socio-environmental conflicts and expropriation of the sea. Currently there are 30 Coastal-Marine RESEXs decreed between the years 1992 and 2018, and 13, are located on the coast of the state of Pará. The mobilizations led by coastal-sea extractive peoples demanding the creation of these Sustainable Use Conservation Units originated from socio-environmental conflicts triggered by the incorporation of the coast of the Pará Amazon into an agenda composed of actions, policies, and initiatives, characterized by literature as the ocean grabbing. The results of the research indicate that it was only in 2008, that is, a little more than a decade after the institutionalization of the first Coastal-Marine RESEXs in Brazil, that the idea of forming an organization to represent the socio-environmental movement emerged. Over the years CONFREM has been expanding its window of action and gaining recognition from the State and Society as a whole. The main agendas defended by CONFREM involve the demand and the monitoring of the processes of creation of new Conservation Units, as well as the access to policies that meet and recognize the specificities of the category. In different participation spaces, such as meetings, forums, and seminars, these leaders of CONFREM of the Coastal-Marine RESEXs of the coast of Pará present a claim directed to academia: the construction of the concept of the maretório. Based on these leaders, it was possible to understand that the maretório, as a concept, would be characterized as the necessary lenses for those who wish to understand the socio-environmental dynamics, which occurs on the coast of the Pará Amazon, of the population segment self-denominated as "coastal-marine extractive peoples," which is linked to the singularity of a way of life based on cultural, political, and economic reproduction amidst the fluidity of the processes of appropriation and use of common resources of coastal and marine environments and ecosystems.